Negar el dogma de la Transsubstanciació. El procés inquisitorial contra Antoni Moxó (1504-1505), el convers que 'no volia rebre lo cors preciós de Jesucrist'. - MOMPÓ, JACOB (Scripta, 2023)
The early 16th century in Valencia witnessed a period of intense persecution against the social minority of Jewish converts. Antoni Moxó, a convert who consistently presented himself publicly as a believing Christian, was discovered by accident. His neighbors felt compelled to save his soul and forced him to receive the sacraments of confession and the Eucharist after he was affected by a transient illness that caused episodes of dementia. Despite his converso origins and 'reprehensible' sexual behaviour, the inquisitors only needed to demonstrate that Moxó did not believe in the dogma of transubstantiation to condemn him to the stake. This study delves into the inquisitorial process of Antoni Moxó in order to explore the life experiences of an unknown person who was condemned to death for refusing to take communion, likely due to his mental state.